Revitalisasi Manajemen Bencana: Pemicu Peningkatan Kinerja Tanggap Darurat dalam Pengurangan Risiko Bencana di Kabupaten Sumedang, Indonesia - Akadun, Akadun; Wardani, Nenden (Universitas Terbuka, 2024)
Disaster management has a vital role in efforts to reduce disaster risk, especially related to human survival. This research aims to analyze the impact of revitalizing disaster management on the effectiveness of disaster risk reduction through emergency response performance in Indonesia. The research method uses descriptive analysis with census techniques as sampling, using questionnaires, documentation and interviews as data collection tools, and applies path analysis as the main analysis technique. The research results show that disaster management has an influence on the effectiveness of reducing the risk of landslides through emergency response performance in Sumedang Regency by 51.90%. Revitalization is needed at every stage of disaster management, starting from pre-disaster, during the disaster, to post-disaster. Even though Indonesia has institutions that handle disasters from the central to regional levels, the challenges of inter-agency coordination and the lack of integration of Regional Spatial Planning (RTRW) and Detailed Spatial Planning (RDTR) policies as part of disaster management still need to be addressed.